“Here, let me do it for you”: Psychological consequences of receiving direct and indirect help in childhood - Sierksma, Jellie; Brummelman, Eddie (Wiley-Blackwell Publishing Ltd, 2025)
What are the psychological consequences of receiving direct and indirect help in childhood? We conducted three preregistered experiments (N = 619, 7–9 years, 80% Dutch, 51% girls, 49% boys, mostly higher socioeconomic status) in the Netherlands (July 2020–July 2022). Children received direct help (correct answer), indirect help (hint), or no help. An internal meta-analysis showed that children who received help felt less competent, liked the task less, and felt more in need of help. Children who received help also sought fewer challenges (Study 3). Effect sizes were modest. Direct and indirect help had largely similar effects, except that children disliked and misreported receiving direct help more. Thus, despite being well-intentioned, direct and indirect help can be discouraging.
Keywords: feedback; motivation; self-perceived ability; unsolicited help; Pediatrics, Perinatology, and Child Health; Education; Developmental and Educational Psychology